Epistemic freedom in Africa: deprovincialization and decolonization by Sabelo J. Ndlovu-Gatsheni - Masixole Booi (University of Johannesburg, 2020)
In this review of Sabelo J. Ndlovu-Gatsheni's Epistemic Freedom in Africa: Deprovincialization and Decolonization, Masixole Booi explains in detail how the book focuses on the history and politics of knowledge production and how Africa has been located on the marginal lines of such 'knowledge production'. Key words: decolonisaiton, politics of knowledge, epistemic freedom, social justice, epistemic justice How to cite this article: Booi, M. 2020. Book review: Ndlovu-Gatsheni, S.J. 2018. Epistemic Freedom in Africa: Deprovincialization and Decolonization. Abingdon, United Kingdom: Routledge. Scholarship of Teaching and Learning in the South. v. 4, n. 1, p. 89-96. April 2020. Available at: https://sotl-south-journal.net/?journal=sotls&page=article&op=view&path%5B%5D=143 This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/